ANALISIS HAK GUNA BANGUNAN YANG TIDAK BISA DIPERPANJANG KARENA PERUBAHAN RENCANA TATA RUANG WILAYAH - Nur Chamid; Nynda Fatmawati (HUKMY : Jurnal Hukum, 2022)
Building Use Rights (BUR) according to Law Number 5 of 1960 Article 35 paragraph 1 concerning Basic Agrarian Regulations is the right to construct and own buildings on land that is not one's own, with a maximum period of 30 years. With the time period determined, the right holder is required to extend the specified period before the validity period ends. In extending the BUR, it is necessary to pay attention to the Regional Spatial Plan that has been determined by the Regional Government where the BUR are located. It will be a separate problem if the Spatial and Regional Planning in the area changes in line with the policies that have been set by the Regional Government, so that the term of the BUR cannot be extended or the period of time can be extended on condition that the holder of the BUR adjusts the building object. by following the Spatial and Regional Layouts that have been determined by the Regional Government. The purpose of this paper is to describe the status and administrative actions of the local government on the BUR which cannot be extended due to changes in the Spatial and Regional Planning. The method used in this research is juridical-empirical law research. Data sources consist of primary and secondary legal materials. The conclusion in this study aims to answer the problems that arise, namely the status and administrative actions of local governments on BUR which cannot be extended due to changes in Spatial and Regional Plans.